Formation of Optimum Portfolio Using Single Index Model (Case Study of Stock LQ 45 Period 2016 - 2019) - Yuliani, Reva; Sutisna, Deden; Oktaviani, Desy; Genia Fatihat, Gita; Hasan Padmanegara, Oliver (International Journal of Psychosocial Rehabilitation, 2020)
Investment is the investment of a number of funds or goods that are expected to provide more results in the future. The purpose of this study is to determine the optimal portfolio with its composition. The method used is the Single Index Model method, and the data used in this study are quantitative data. Based on the results of this study, it can be concluded that the optimal portfolio produced 3 optimal shares of 31 shares that were sampled in this study, including ANTM 22%, SRIL 36%, and INCO 42%, with expected portfolio returns of 0.0546 and a portfolio standard deviation level of 0,1563.